Misfit dislocation dipoles in coated fibrous composites - Wang, Xu (2016)
We investigate the stability of a misfit screw dislocation dipole in a coated fibrous composite. The fiber is stiffer whereas the coating is more compliant than the matrix. A critical coating thickness is identified for given material parameters of the composite. For a compliant coating below the critical thickness, there exist an inner unstable and an outer stable equilibrium position in the matrix for the dislocation dipole. However, for a compliant coating above the critical thickness, the dislocation dipole will be attracted to the coating–matrix interface. If the coating thickness is greater than the inclusion radius, the dislocation dipole cannot lodge in the matrix no matter what values of the material parameters are chosen.